Age-related changes of hepatic clearances of cytochrome P450 probes, midazolam and R-/S-warfarin in combination with caffeine, omeprazole and metoprolol in cynomolgus monkeys using in vitro–in vivo correlation. (3rd November 2014) - Koyanagi, Takashi; Nakanishi, Yasuharu; Murayama, Norie; Yamaura, Yoshiyuki; Ikeda, Kanami; Yano, Koji; Uehara, Shotaro; Utoh, Masahiro; Kim, Soonih; Uno, Yasuhiro; Yamazaki, Hiroshi
Abstract: 1. Pharmacokinetics of human cytochrome P450 probes (caffeine, racemic warfarin, omeprazole, metoprolol and midazolam) were investigated after single intravenous and oral administrations at doses of 0.20 and 1.0 mg kg −1, respectively, in combination to three young (3-year-old) and three aged (16-year-old) cynomolgus monkeys. 2. The plasma concentrations of caffeine and R -/ S -warfarin decreased slowly in a monophasic manner, but those of omeprazole, metoprolol and midazolam decreased rapidly, in a similar manner to those as reported for pharmacokinetics in humans. 3. The mean maximum concentrations of R - and S -warfarin (4.6 and 3.7 µg/mL, respectively) in aged monkeys after oral administration were significantly higher than those in young monkeys (3.3 and 2.7 µg/mL). The mean clearance (CL) values of midazolam in aged monkeys (9.5 mL/min/kg) were significantly lower than those in young monkeys (13 mL/min/kg). 4. Individual intrinsic CL values for omeprazole ( r  = 0.29) and metoprolol ( r  = 0.30) of individual monkey livers were inversely correlated with their ages significantly ( p  < 0.05) in liver microsomes prepared from 55 cynomolgus monkeys. 5. These results suggest that cynomolgus monkeys could be a good model for humans, especially with particular characteristics in reduced CLs of some human P450 substrates by aging.